Censorship v. Freedom of Speech in English-Speaking Countries. Cultural, Political and Historical Perspectives - Nicole Cloarec; Émilie Dardenne (Revue LISA)
Since the 1990s the complexity of censorship as a phenomenon has been emphasised, as it grows both in importance and currency in the modern world. Political rhetoric enables censorship to go well beyond mere acts of repressive control imposed by governments or legal authorities over free expression. In Western democracies, and especially in English-speaking countries, which were among the first to vindicate free speech, censorship has been increasingly reassessed as the result of a compromise, rather than a fixed frontier defining freedom and repression. Instead it seems to offer a space within which negotiations are permanently enacted between individuals and groups over political, social and cultural practices. Thus, while the terms of this compromise are also problematised and questioned, it has become imperative for a number of academic disciplines such as history, civilisation or philosophy to track down the different practices of censorship, its arguments and its implications. This volume aims precisely at broadening and enriching perspectives to grasp some new possible theoretical underpinnings of the concept.